2012
DOI: 10.1016/j.carj.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Risk Factors for Contrast-Induced Nephrotoxicity in Outpatients Undergoing Intravenous Contrast-Enhanced Computed Tomography Studies

Abstract: In an ambulatory outpatient population, many patients presenting for outpatient CECT studies will have risk factors for CIN or for kidney function impairment (low eGFR) at baseline. Kidney function assessment, therefore, is indicated in this patient population before CECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…Although we pooled the electronic data of a very large population, this was not a random sample of the target population; thus we cannot say that it is generalizable to all CECT patients. Carstensen et al (22) reported a prevalence of renal insufficiency that was very similar to this study. However, the study participants could have had more risk factors than ordinary CECT patients, as we selected patients from tertiary hospitals, which might still result in an over-estimation of the prevalence of risk factors.…”
Section: Discussionsupporting
confidence: 89%
“…Although we pooled the electronic data of a very large population, this was not a random sample of the target population; thus we cannot say that it is generalizable to all CECT patients. Carstensen et al (22) reported a prevalence of renal insufficiency that was very similar to this study. However, the study participants could have had more risk factors than ordinary CECT patients, as we selected patients from tertiary hospitals, which might still result in an over-estimation of the prevalence of risk factors.…”
Section: Discussionsupporting
confidence: 89%
“…48 In a survey study with 200 patients undergoing CECT, 69% of the patients reported risk factors for contrast-induced nephrotoxicity or kidney function impairments. 49 On the other hand, mild enhancement and pseudoenhancement can be observed in certain small cyst cases and low-grade RCCs on CECT, which makes it difficult to make a differential diagnosis. 50,51 As a radiation-free imaging approach with low incidences of side effects, CEUS can be used in patients with renal insufficiency and obstruction and has been considered a good alternative for renal cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…En av de största riskfaktorerna för KMN är om patienten har kronisk njursjukdom (Owen, Hiremath, Myers, Fraser-Hill & Barrett, 2014). Förekomsten av KMN och riskfaktorer hos patienter som genomgått intravenös jodkontrastundersökning visar ett stort samband mellan KMN och förekomst av njurinsuffiens (Carstensen, Keer, Rempel, Jeon & Barrett, 2012;Moos, Stoker, Nagan, de Weijert, van Vemde & Bipat, 2013). I de nationella rekommendationerna för jodkontrastmedel, utarbetat av SURF, framgår att risken för KMN kan vara svår att förutse på grund av olika riskfaktorer, olika GFR-nivåer, olika kontrastmedelsdoser, samt kombinationen av dessa.…”
unclassified